ASAL USUL DAN PERKEMBANGAN PESANTREN DI INDONESIA - Syah, Zaimir; Iswantir, Iswantir (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
Islamic boarding schools are traditional educational institutions led by a kyai or cleric. It is in this pesantren that the santri are confronted with various branches of religious knowledge which originate from classical books. For this reason, the purpose of writing this article is to find out the origins of the development of Islamic boarding schools in Indonesia. This research includes qualitative research with the type of library research. The results of the study show that as the oldest Islamic educational institution, the historical development of Islamic boarding schools has non-classical teaching models, namely the education system method with the wetonan and sorogan teaching methods. Islamic boarding schools today can be divided into two types, namely traditional Islamic boarding schools (salafi) with a mystical environment and modern Islamic boarding schools (khalafi). the existence of the ummah from attacks and physical and mental oppression by the colonialists for several centuries. Islamic boarding schools, which were initially carried out in a simple way, turned out to play a significant role in the history of Islamic education in Indonesia, and gave birth to many famous figures.